Слідчі (розшукові) дії як складова досудового розслідування - Салманов, О. В.; Salmanov, O. V.; ORCID: http://orcid.org/0000-0001-9421-5085 (Наше право. - 2020. - № 4. - С. 105-110, 2020)
Охарактеризовано наукові та нормативно-правові джерела, що регламентують здійснення досудового розслідування взагалі та слідчих (розшукових) дій зокрема. З’ясовано, що слідчі (розшукові) дії є основним засобом доказування, інструментом пізнавальної діяльності з розслідування кримінальних правопорушень. Розглянуто наукові погляди стосовно тлумачення терміну «слідча (розшукова) дія». Виокремлено властивості слідчих (розшукових) дій, визначено їх значення в досудовому розслідуванні та сформульовано авторське визначення поняття слідчих (розшукових) дій.

The article describes the scientific and regulatory sources governing the implementation of pretrial investigation in general and investigative (investigative) actions in particular. It was found that investigative (search) actions are the main means of proof, a tool of cognitive activity in the investigation of criminal offenses. It is established that the legislative definition of investigative (investigative) action is imperfect and does not fully reflect its essence as a means of obtaining evidence during the pre-trial investigation. Scientific approaches to the definition of the main features and concepts of investigative (investigative) actions in the professional literature are analyzed and on their basis a more detailed interpretation of the term “investigative (investigative) action” is proposed. It is established that the main features of the investigative (search) action are a clear regulation of the grounds, procedure and its authorized subjects by the rules of criminal procedure legislation; focus on finding, obtaining and verifying evidence and information about them. Investigative (search) action is defined as a set of cognitive and search actions carried out by authorized subjects on the grounds and in the manner prescribed by the criminal procedure law, in order to form the evidence base.

Охарактеризованы научные и нормативно-правовые источники, регламентирующие осуществление досудебного расследования и следственных (розыскных) действий в частности. Установлено, что следственные (розыскные) действия являются основным средством доказывания, инструментом познавательной деятельности по расследованию уголовных правонарушений. Рассмотрены научные взгляды по поводу толкования термина «следственное (розыскное) действие». Выделены свойства следственных (розыскных) действий, определено их значение в досудебном расследовании и сформулировано авторское определение понятия следственных (розыскных) действий.
Салманов, О. В. Слідчі (розшукові) дії як складова досудового розслідування / Салманов Олексій Валерійович // Наше право. - 2020. - № 4. - С. 105-110. - DOI: 10.32782/NP.2020.4.16.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; досудове розслідування; pre-trial investigation; досудебное расследование; слідча (розшукова) дія; investigative (research) action; следственное (розыскное) действие; кримінальне провадження; criminal proceedings; уголовное производство; кримінальне процесуальне законодавство; criminal procedural legislation; уголовное процессуальное законодательство